Oil Market Efficiency, Quantity of Information, and Oil Market Turbulence - Marc Gronwald; Sania Wadud; Kingsley Dogah (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper analyses the informational efficiency of the WTI crude oil markets using a recently proposed quantitative measure for market inefficiency. The procedure measures the extent to which observed oil price behaviour deviates from the Random Walk benchmark which represents an efficient market. The key findings are, first, that crude oil market inefficiency varies over time. Second, abrupt increases in inefficiency occur during extreme episodes such as the price downturns witnessed in 2008, 2014, and early 2020, as well as the begin of the Ukraine war in 2022. Third, the paper puts forward the interpretation of oil market inefficiency as oil market turbulence. This occurs when the quantity of information the market has to process is exceptionally high. Fourth, the paper demonstrates that oil market turbulence (or the drivers behind it) have negative macroeconomic consequences.
Keywords: C22; E30; G14; Q02; Q31; 330; crude oil markets; efficient market hypothesis; quantity of information; fractional integration